2014
DOI: 10.1126/scisignal.2005032
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Profiling of the Transcriptome, Cistrome, and Epigenome in the Cellular Response to Ionizing Radiation

Abstract: The DNA damage response (DDR) is a vast signaling network that is robustly activated by DNA double-strand breaks, the critical lesion induced by ionizing radiation (IR). Although much of this response operates at the protein level, a critical component of the network sustains many DDR branches by modulating the cellular transcriptome. Using deep sequencing, we delineated three layers in the transcriptional response to IR in human breast cancer cells: changes in the expression of genes encoding proteins or long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 86 publications
9
37
0
Order By: Relevance
“…4e). Confirmatory analyses using additional available data1556 showed that RP11-115D19.1 was induced in human fibroblasts treated with the DNA damaging agent doxorubicin and reduced in response to TP53 siRNA in breast cancer cells exposed to ionizing radiation, although levels were low in these cells (Supplementary Fig. 8).…”
Section: Resultsmentioning
confidence: 84%
“…4e). Confirmatory analyses using additional available data1556 showed that RP11-115D19.1 was induced in human fibroblasts treated with the DNA damaging agent doxorubicin and reduced in response to TP53 siRNA in breast cancer cells exposed to ionizing radiation, although levels were low in these cells (Supplementary Fig. 8).…”
Section: Resultsmentioning
confidence: 84%
“…Yet, it is likely that other cell lines also exhibit an increase in the p53 apoptotic threshold over time, as both HeLa cells and HMEC-1 cells induce genes in the IAP family after DNA damage (Figure S5B, C). An increase in the expression of IAP genes after DNA damage was also found in breast (Rashi-Elkeles et al, 2014) and thyroid (Tirrò et al, 2006) cancer lines. However, not all thyroid lines show increased induction of IAP genes, suggesting that the increase in the p53 apoptotic threshold with time might exist in some, but not all cell lines.…”
Section: Discussionmentioning
confidence: 81%
“…In the recent past, lincRNAs have been shown to play a role in gene regulation and in a plethora of other biological processes (Cheetham et al, 2013;Dinger et al, 2008;Xu et al, 2013). However, until now only a few lincRNAs have been implicated in the DNA damage response (Liu and Lu, 2012;Rashi-Elkeles et al, 2014;Younger et al, 2015). Our transcriptome analysis enabled us to reveal many lincRNAs that are differentially expressed upon UV irradiation, which might be crucial regulators of the stress response and be interesting candidates for further mechanistic analysis.…”
Section: Discussionmentioning
confidence: 92%
“…H3S28 phosphorylation is furthermore involved in the regulation of RNA-polymerase-IIIdependent transcription (Zhang et al, 2011). Given that many long non-coding RNAs (lncRNAs) are deregulated upon X-ray irradiation and doxorubicin treatment in mammalian fibroblasts (Rashi-Elkeles et al, 2014;Younger et al, 2015), and several lncRNAs have been implicated in the DNA damage response (Huarte et al, 2010;Liu and Lu, 2012;Negishi et al, 2014;Wan et al, 2013), it is likely that lncRNAs also play a crucial role in modulating gene expression upon UV irradiation.…”
Section: Introductionmentioning
confidence: 99%